Comparison of electrophoretic deposition kinetics of graphene oxide nanosheets in organic and aqueous solutions. Issue 9 (15th June 2018) - Hajizadeh, A.; Aliofkhazraei, M.; Hasanpoor, M.; Mohammadi, E.
Abstract: Electrophoretic deposition (EPD) of Graphene Oxide (GO) has been used in several applications but in a few studies, the kinetics of the process has been considered. In the present work, the EPD of GO in organic (ethanol) and aqueous (deionized water) solutions was carried out without any additives while in-situ measurement of mass and current density were performed. Furthermore, the resistance of the deposit, voltage drop, and the effective field along suspension during EPD have been studied. These results, alongside current density plots, indicated the reduction of GO on the surface of the anode in deionized water. Comparison of the mass results to the Hamaker model indicates good compatibility in deionized water across lower voltages, yet the differences tend to grow as the voltage is increased. However, in ethanol, parabolic changes in mass, lead to an incompatibility of mass variations and the model. The microstructure and thickness of the coatings were investigated by scanning electron microscopy (SEM) indicated that the maximum thickness of the coatings achieved in the appropriate voltage was about 3 µm. It can be concluded that the type of solution is a critical factor in the EPD of GO which can affect the process and properties of the final coating. Graphical abstract: